EVALUATION OF THE EFFICIENCY OF DEVELOPMENT BANKS ACTIVITIES AS AN IMPORTANT FACTOR OF ECONOMIC SUCCESS (ON THE EXAMPLES OF GERMAN, ASIAN AND AFRICAN DEVELOPMENT BANKS) - S. S. Matveevskii (Вестник университета)
The existence of a system for assessing the activities of development banks is a necessary condition for a significant contribution of banks to economic development. The article deals with the experience of evaluating the effectiveness of projects and activities of development banks on the examples of the German development Bank, the Asian development Bank and the African development Bank. It has been revealed, that development banks for the evaluation of projects, their activities apply financial and socio-economic indicators, which are used to improve the work of development banks. The basic requirements for the evaluation of projects and activities of development banks have been formulated. The practical experience of the German development Bank, the Asian development Bank and the African development Bank can be used by Vnesheconombank, which is confirmed by scientific studies of Russian authors.